A Comparative Study on the Psychological Health of Frontline Health Workers in Wuhan Under and After the Lockdown - Qiu, Xiuli; Lan, Yan; Miao, Jinfeng; Wang, Hui; Wang, He; Wu, Jianhong; Li, Guo; Zhao, Xin; Cao, Ziqin; Mei, Junhua; Sun, Wenzhe; Zhu, Zhou; et al. (Frontiers in Psychiatry, 2021)
Background The coronavirus disease-2019 (COVID-19) outbreak and a three-month lockdown of Wuhan may have had a long-term impact on the mental health of frontline healthcare workers (HWs). However, there is still a lack of comparative studies on the mental health of front-line HWs in the initial phase of the lockdown and one month after the lifting of the lockdown. Methods We recruited 1717 HWs during the initial phase of the lockdown and 2214 HWs one month after the lifting of the lockdown, and their baseline characteristics and psychiatric health in these two phases were compared. Furthermore, Pearson's Chi-square test and multivariate logistic regression analysis were used to determine the possible risk factors associated with depressive symptoms in the front-line HWs. Results Compared with the initial phase of the lockdown, the proportion of HWs with anxiety symptoms and stress decreased, while the proportion of HWs with depressive symptoms increased a month after the lifting of the lockdown. Male sex, exercise habit, comorbidities, and having family members or relatives with suspected or confirmed COVID-19 infection were significantly related to the increased incidence of depressive symptoms during the initial phase of the lockdown. Comorbidities, negative effect of media coverage, working > 4 days a week, lower annual household income, and deteriorating relationships with family members were associated with depressive symptoms a month after the lifting of the lockdown. Conclusion The increased proportion of HWs with depressive symptoms one month after the lifting of the lockdown suggested that mental health of front-line HWs should be a top-priority issue, not only during, but also after the pandemic.